EVALUASI WORKSHOP PENINGKATAN KEMAMPUAN PENYUSUNAN PERENCANAAN PEMBELAJARAN BERMUATAN LITERASI KEAGAMAAN LINTAS BUDAYA (LKLB) MENGGUNAKAN MODEL KIRKPATRICK PADA GURU-GURU DI KOTA MALANG - Hidayati, Ririn Eva; Nine Adien , Maulana (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2025)
Abstract This study aims to evaluate the effectiveness of a workshop in enhancing teachers’ ability to develop learning plans that incorporate Cross-Cultural Religious Literacy (CCRL) in Malang City, utilizing the robust Kirkpatrick evaluation model. The research method employed is evaluative, utilizing a mixed-methods approach that encompasses four levels of Kirkpatrick evaluation: reaction, learning, behaviour, and results. The data sources for this study consisted of 30 teachers from various schools and madrasahs in Malang City, who were selected through purposive sampling techniques based on a minimum of three years of teaching experience and involvement in diversity-based learning practices. Data were collected through pre-tests and post-tests, observations, interviews, daily reflections, and surveys from both students and principals. The results showed that at the reaction level, more than 90% of participants were satisfied with the implementation of the workshop. At the learning level, there was a significant increase in understanding the concept of CCRL, as evidenced by a post-test score that was significantly higher than the pre-test score (p < 0.05). At the behavioural level, teachers began to implement inclusive learning based on CCRL in the classroom. At the outcome level, students reported a more inclusive classroom atmosphere, one that respects differences and is participatory. This positive impact on students should encourage educators, researchers, and policymakers about the potential of the workshop. Supporting factors for the workshop’s success included high participant motivation and a training design based on reflective practice. At the same time, the main obstacles were time constraints and variations in participants’ initial abilities. These findings indicate that the cross-cultural religious literacy workshop, evaluated using the Kirkpatrick model, was effective in enhancing teachers’ overall professional competence while also having a positive impact on learning practices and fostering a more tolerant and inclusive classroom climate. Abstrak Penelitian ini bertujuan untuk mengevaluasi efektivitas workshop peningkatan kemampuan penyusunan perencanaan pembelajaran bermuatan Literasi Keagamaan Lintas Budaya (LKLB) bagi guru-guru di Kota Malang menggunakan model evaluasi Kirkpatrick. Metode penelitian yang digunakan adalah evaluatif dengan pendekatan mixed methods, mencakup empat level evaluasi Kirkpatrick: reaksi, pembelajaran, perilaku, dan hasil. Sumber data penelitian ini adalah 30 guru dari beberapa sekolah dan madrasah di Kota Malang yang dipilih melalui teknik purposive sampling, dengan kriteria pengalaman mengajar minimal tiga tahun dan keterlibatan dalam praktik pembelajaran berbasis keberagaman. Data dikumpulkan melalui pre-test dan post-test, observasi, wawancara, refleksi harian, serta survei siswa dan kepala sekolah. Hasil penelitian menunjukkan bahwa pada level reaksi, lebih dari 90% peserta merasa puas terhadap pelaksanaan workshop. Pada level pembelajaran, terjadi peningkatan signifikan dalam pemahaman konsep LKLB, dengan skor post-test yang jauh lebih tinggi dibandingkan pre-test (p < 0,05). Pada level perilaku, guru mulai mengimplementasikan pembelajaran inklusif berbasis LKLB di kelas. Sementara pada level hasil, siswa melaporkan suasana kelas yang lebih inklusif, menghargai perbedaan, dan partisipatif. Faktor pendukung keberhasilan workshop meliputi motivasi tinggi peserta dan desain pelatihan berbasis praktik reflektif, sedangkan kendala utamanya adalah keterbatasan waktu dan variasi kemampuan awal peserta. Temuan ini menunjukkan bahwa workshop berbasis literasi keagamaan lintas budaya yang dievaluasi dengan model Kirkpatrick efektif dalam meningkatkan kompetensi profesional guru secara menyeluruh, serta berdampak positif pada praktik pembelajaran dan iklim kelas yang lebih toleran dan inklusif.